Proposals for Annual Plan 1971-72 Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1971)
The Andaman and Nicobar consists op 348 islands, of which only 31 islands have yet been inhabited. A programme for populating these island is in hand under the Accelerated Development programme.
Andaman and Nicobar Administration
Andaman and Nicobar Administration